Xanthoria parietina polysaccharides : isolation, characterization and influence on murine macrophages under in vitro conditions - Zalilawati Mat Rashid
In this study, polysaccharides from Xanthoria parietina, a wide spread lichen from central Europe, were isolated, purified and analyzed concerning the structural features, in combination with functional investigation of the influence on ,?1urine macrophage cell line RAW264.7 in vitro. Defatted dried lichen (140 g, WT) was submitted to consecutive cold water (4°C, 12 h), freezing (-20°C) and thawing (room temperature), hot water (100°C) as well as alkaline (0.5: M aq. NaOH) extractions (each in triplicate). Only hot aqueous extract, XH (2.8%, W/WT) was further fractionated by ion exchange chromatography to yield mainly H-1 (0.7%) and H-2 (0.4%) (W/WT) fractions. Chromatographic purification of the fractions by gel permeation chromatography yielded polysaccharides H-1-3 (0.39%) and H-2-1 (0.07%) (W/WT) with molecular weights Mwof 13.7 and 525 kDa respectively, prior to ethanol precipitation, dialysis and lyophilisation. Monomers composition analysis by HPAEC-PADand GC-MSrevealed that H-1-3 consisted mainly of glucose (> 98%), while H-2-1 was composed of man nose (74.3%), galactose (14.1%), glucose (9.8%) and rhamnose (1.8%) as well as trace of arabinose. O-/L-configuration of diastereomers analyzed by capillary zone elactrophoresis (CZE) as well as the anomeric configuration by lH- and 13CNMR indicated the presence «-0- glucose in H-1-3 and c-D-manncse, «-0- galactose, u-D-glucose and c-t-Rhap in H-2-1. Subsequently, linkage sequences were determined by GC-MS analysis of partially methylated alditol acetates, nano-ESI QTOF-MS/MS analysis of oligosaccharides and 2D-NMR analysis of native polysaccharides and oligosaccharides. In nano-ESI-Q- TOF MS/MS analysis, the use of silver adducts in positive-ion mode settings was established and found to be capable of rising A- and X-type fragment ions generated from cross-ring cleavages, together with the rise of 8- and Y-type ions from the glycosidic bonds cleavages of the oligosaccharides prepared from H-1-3 but not H-2-1. For H-2-1, the use of chloride adduct in negative-ion mode settings was better capable in rising similar type of fragment ions.